Behavioral Disorder amongst Adolescents Attending Secondary School in Southeast Nigeria - Chinawa, J. M. (Hindawi Publishing Corporation, 2014)
Background. Adolescents are prone to various forms of behavioral problems. These behavioral issues in adolescents can have serious consequences for the adolescents. Objectives. The objectives of the study are to determine the causative factors of adolescent problems and specific manifestations. Methods. Behavioral problems were investigated using a random sampling of adolescents from secondary schools in southeast Nigeria from February to April, 2014. A self-administered questionnaire was developed from Health Kids Colorado Questionnaire. Results. A total of 763 subjects completed the questionnaire. Adolescents who reported to have used tobacco 3 to 5 and 6 to 9 times during the last 30 days are just 3.14% and 3.4%, respectively. Nineteen (2.49%) adolescents claimed that they have had sex before but not in the last 3 months. Adolescents who attempted suicide are from 15 years and peaked at 18. Eighty-three (11%) adolescents who are 15 years old attempted suicide in a year; this peaks at 17 years where 235 (30.8%) committed suicide. Majority of adolescents with behavioral disorder are from the upper class family. Conclusion. This study revealed that adolescents exhibit several forms of behavioral problems.